Al-tafsir al-tawhidi: a study of al-Turabi's approach to quranic exegesis - Ibrahim , Esam Eltigani Mohamed (2013)
Although al-Turabi is not known as a Quranic exegetist (mufassir) as such, he is deeply interested in Quranic studies. He commented on twenty chapters of the Quran in what he named “al-Tafsir al-Tawhidi”. Before introducing al-Turabi‟s al-Tafsir al-Tawhidi, this research first provides a short biographical sketch of his life and attainments, the reasons that led al-Turabi to engage in this interpretive project, his organizational structure, as well as the sources he drew upon to complete his work. This article is both analytical and inductive in nature.